Correlación entre los niveles de Hemoglobina Glicada y las enzimas antioxidantes, en pacientes con Diabetes Mellitus Tipo 2 - Vergaray, L. (2000)
It has been determined Glycated A1c haemoglobin, Superóxido Dismutase, Glutation peroxidase and Malondialdehide levels in 25 patients with Diabetes mellitus type 2, whom participate in the Education Program for Diabetic Patients, from Arzobispo Loayza Hospital, they were confront with 15 persons apparently healthful control group. There is a positive correlation between Glycated A1c haemoglobin - Superoxido Dismutase (r=0,164, p<0.05) and Glycated A1c haemoglobin - Malondyaldehíde (r=0.432, p<0.05) levels. We deduce that a high level of Malondialdehíde is associate with the Diabetes mellitus type 2 complications, for a high free radicals generation, that conduce to antioxidantes system desequilibrium, resulting low Ievels Glutation peroxidase, normal or high slightly level Superoxido Dismutase confront control group.